Terrorism, ethnicity and Islamic extremism in Sahel - Galito, Maria Sousa (2014)
Terrorism is a threat in the Sahel region, where peoples and rulers seem to be losing control of the situation. Yet, the true origins of the instability are questionable. Ethnical conflicts and the religious differences, especially those related with the spreading of Islamic extremism among the local population, are two of the main reasons. This research paper analyzes different theories so as to attain some answers to these issues.